Negative electrode for non-aqueous electrolyte secondary battery and non-aqueous electrolyte secondary battery
Patent Information
- Application Number
- JP2021507245
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-03-19
- Filing Date
- 2020-03-11
- Publication Date
- 2025-03-03
- Estimated Expiration
- 2040-03-11
AI Technical Summary
【0009】 本発明によれば、シリコン含有材料を含む負極を備える非水電解液二次電池のサイクル特性を高めることができる。 本発明の新規な特徴を添付の請求の範囲に記述するが、本発明は、構成および内容の両方に関し、本発明の他の目的および特徴と併せ、図面を照合した以下の詳細な説明によりさらによく理解されるであろう。
Smart Images

Figure 0007637900000004 
Figure 0007637900000001 
Figure 0007637900000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a negative electrode containing a silicon-containing material and a nonaqueous electrolyte secondary battery including the negative electrode. [Background technology]
[0002] A non-aqueous electrolyte secondary battery, such as a lithium ion secondary battery, includes a positive electrode, a negative electrode, and a non-aqueous electrolyte. The negative electrode includes a negative electrode mixture that includes a negative electrode active material that can electrochemically absorb and release lithium ions. In order to increase the capacity of the battery, the use of a silicon-containing material as the negative electrode active material has been considered. The non-aqueous electrolyte includes a lithium salt, and lithium hexafluorophosphate (LiPF6) is widely used as the lithium salt.
[0003] Components in the non-aqueous electrolyte may react with moisture in the battery to form hydrogen fluoride, which easily decomposes silicon-containing materials and can easily cause deterioration of the cycle characteristics due to the degradation caused by the decomposition of the silicon-containing materials.
[0004] In response to this, Patent Document 1 proposes adding glass powder containing silicon dioxide and an oxide of an alkaline earth metal to the anode, etc., in order to reduce hydrogen fluoride. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Special Publication No. 2015-532762 Summary of the Invention [Problem to be solved by the invention]
[0006] As a method of adding glass powder described in Patent Document 1, it is considered to prepare a negative electrode using a negative electrode slurry in which a negative electrode mixture containing a silicon-containing material and glass powder is dispersed in water. However, the negative electrode slurry containing glass powder is easily shifted to a basic state, and the silicon-containing material dissolves and deteriorates under basic conditions, which may result in a decrease in cycle characteristics. [Means for solving the problem]
[0007] In view of the above, one aspect of the present invention relates to a negative electrode for a non-aqueous electrolyte secondary battery, comprising: a negative electrode mixture including a negative electrode active material capable of electrochemically absorbing and desorbing lithium ions, a negative electrode additive, and an acrylic resin, wherein the negative electrode active material includes a silicon-containing material, the negative electrode additive includes at least silicon dioxide and an oxide of a Group 2 element, the oxide of the Group 2 element including at least one selected from the group consisting of BeO, MgO, CaO, SrO, BaO, and RaO, the acrylic resin includes at least a unit of a (meth)acrylate, and a content of the oxide of the Group 2 element in the negative electrode additive is less than 20 mass % with respect to the total amount of the negative electrode additive.
[0008] Another aspect of the present invention relates to a nonaqueous electrolyte secondary battery comprising a positive electrode, a negative electrode, and a nonaqueous electrolyte, the negative electrode being the above-mentioned negative electrode. Effect of the Invention
[0009] According to the present invention, it is possible to improve the cycle characteristics of a nonaqueous electrolyte secondary battery having a negative electrode containing a silicon-containing material. The novel features of the present invention are set forth in the appended claims, but the present invention, both in terms of structure and content, together with other objects and features of the present invention, will be better understood from the following detailed description taken in conjunction with the drawings. [Brief description of the drawings]
[0010] [Figure 1] 1 is a schematic perspective view of a nonaqueous electrolyte secondary battery according to one embodiment of the present invention, with a portion cut away; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The negative electrode for a non-aqueous electrolyte secondary battery according to one embodiment of the present invention includes a negative electrode mixture containing a negative electrode active material capable of electrochemically absorbing and releasing lithium ions, a negative electrode additive, and an acrylic resin. The negative electrode active material contains a silicon-containing material. The negative electrode additive contains at least silicon dioxide and an oxide of a Group 2 element, and the oxide of the Group 2 element contains at least one selected from the group consisting of BeO, MgO, CaO, SrO, BaO, and RaO. The acrylic resin contains at least a unit of a (meth)acrylate salt. The content of the oxide of the Group 2 element in the negative electrode additive is less than 20 mass% with respect to the total amount (100 mass%) of the negative electrode additive.
[0012] By including the above-mentioned negative electrode additive in the negative electrode mixture, the deterioration of the silicon-containing material due to hydrogen fluoride generated during charging and discharging after the battery is manufactured is suppressed. In addition, by adjusting the content of the oxide of the second element in the negative electrode additive to the above-mentioned range and including the above-mentioned acrylic resin in the negative electrode mixture, the shift of the negative electrode slurry to basicity due to the negative electrode additive is significantly suppressed. By suppressing the shift of the negative electrode slurry to basicity, the dissolution deterioration of the silicon-containing material and the decrease in cycle characteristics due to the deterioration are significantly suppressed.
[0013] (Negative Electrode Additive) The negative electrode additive contains at least silicon dioxide (SiO2) and an oxide of a Group 2 element, including at least one selected from the group consisting of BeO, MgO, CaO, SrO, BaO, and RaO. Hydrogen fluoride generated due to decomposition of the non-aqueous electrolyte by moisture in the battery reacts with silicon dioxide and the oxide of the Group 2 element in the negative electrode additive to generate fluoride. The amount of hydrogen fluoride is reduced by the negative electrode additive, so that the dissolution deterioration of the silicon-containing material is suppressed and the cycle characteristics are improved. For example, when BaO is used, BaSiF6 is generated. The negative electrode additive is used, for example, as a powdered glass containing silicon dioxide and an oxide of the Group 2 element.
[0014] In the above-mentioned negative electrode additive, when the content of the oxide of the Group 2 element is less than 20 mass% based on the total amount of the negative electrode additive, hydrogen fluoride can be sufficiently absorbed while suppressing the shift of the negative electrode slurry to basicity, and the dissolution deterioration of the silicon-containing material can be reduced. When the above-mentioned acrylic resin and the negative electrode additive containing a specific amount of the oxide of the Group 2 element are used, the cycle characteristics are significantly improved.
[0015] The content of the oxide of the Group 2 element in the negative electrode additive is, for example, 1% by mass or more and less than 20% by mass, preferably 3% by mass or more and 19.5% by mass or less, more preferably 10% by mass or more and 19.5% by mass or less, based on the total amount of the negative electrode additive. When the content of the oxide of the Group 2 element in the negative electrode additive is 1% by mass or more based on the total amount of the negative electrode additive, hydrogen fluoride is sufficiently absorbed by the negative electrode additive. When the content of the oxide of the Group 2 element in the negative electrode additive is less than 20% by mass based on the total amount of the negative electrode additive, the Group 2 element contained in the negative electrode additive is less likely to be dissolved as an ion in the negative electrode slurry (dispersion medium), and the shift of the negative electrode slurry to basicity is suppressed. In addition, since the Group 2 element is more likely to exist as an oxide in the negative electrode slurry, the hydrogen fluoride absorption effect is sufficiently obtained.
[0016] The content of the oxide of the Group 2 element in the negative electrode additive (mass ratio to the total amount of the negative electrode additive) can be determined by the following method. The battery is disassembled, the negative electrode is removed, washed with a non-aqueous solvent such as ethylene carbonate, dried, and then the cross section of the negative electrode mixture layer is processed by a cross section polisher (CP) to obtain a sample. A field emission scanning electron microscope (FE-SEM) is used to obtain a backscattered electron image of the sample cross section, and the cross section of the negative electrode additive particle is observed. An Auger electron spectroscopy (AES) analyzer is used to perform qualitative and quantitative analysis of elements in a certain area in the center of the cross section of the observed negative electrode additive particle, and the mass of the group 2 element M is obtained (accelerating voltage 10 kV, beam current 10 nA). Assuming that all of the group 2 element M is oxide MO, the amount of M obtained by the above analysis is converted to the amount of MO. An analysis is performed on the 10 observed negative electrode additive particles, and the average of the calculated amounts of MO is taken as the mass W1 of the oxide of the group 2 element.
[0017] In the above analysis, the mass of the Group 2 element M as well as the mass of other elements Q (alkali metal elements such as Si and Na, Al, etc.) other than the Group 2 element M are determined. Assuming that all of the elements Q are oxides of element Q (SiO2, Na2O, Al2O3, etc.), the mass of element Q is converted to the mass of the oxide of element Q. The observed 10 negative electrode additive particles are analyzed, and the average value of the calculated mass of the oxide of element Q is defined as the mass of the oxide of element Q, W2. The sum of W1 and W2 is defined as the total amount of the negative electrode additive, W0. (W1 / W0)×100 is calculated to obtain the content of the oxide of the Group 2 element in the negative electrode additive (mass ratio to the total amount of the negative electrode additive).
[0018] The average particle size of the negative electrode additive particles (approximately 0.3 μm or more and 3 μm or less) is determined by the silicon-containing material (SiO x The average particle size of the anode additive particles is smaller than that of the silicon-containing material particles (5 μm or more, 10 μm or less), and silicon particles are dispersed inside the particles of the silicon-containing material. By observing the particle size and the inside of the particle, it is possible to distinguish between the anode additive particles and the silicon-containing material. In other words, the anode additive can be silicate particles or glass particles that do not contain silicon particles. In observing and analyzing the cross-section of the above sample, a carbon sample stage can be used to fix the sample in place to prevent the diffusion of Li. In order to prevent the cross-section of the sample from being altered, a transfer vessel can be used to hold and transport the sample without exposing it to the atmosphere.
[0019] The total content of silicon dioxide and the oxide of the Group 2 element in the negative electrode additive is, for example, 80 mass% or more, and may be 85 mass% or more, based on the total amount of the negative electrode additive. In the negative electrode additive, the mass ratio of the oxide of the Group 2 element to silicon dioxide is, for example, 1 / 3 or more and 50 or less.
[0020] The oxide of the Group 2 element preferably contains at least one selected from the group consisting of BaO and CaO, in which case the hydrogen fluoride trapping effect is remarkable and cycle characteristics are further improved.
[0021] The negative electrode additive may further include an oxide of an alkali metal element. The negative electrode additive may further include other components such as Al2O3, B2O3, and P2O5. The oxide of the alkali metal element may include at least one selected from the group consisting of Li2O, Na2O, and K2O. Among them, the oxide of the alkali metal element is preferably Na2O.
[0022] When the negative electrode additive further contains Na2O, the cycle characteristics are more likely to be improved. In this case, Na is more likely to be dissolved from the negative electrode additive into the electrolyte, and the negative electrode additive from which Na has dissolved becomes more reactive and more likely to react with hydrogen fluoride to form fluorides, so that the dissolution and deterioration of silicon-containing materials caused by hydrogen fluoride is more effectively suppressed. In addition, Na dissolved from the negative electrode additive can be a component of the SEI (Solid Electrolyte Interphase) film formed on the surface of the negative electrode active material during charging and discharging. The SEI film containing Na together with Li is more likely to have a lower resistance than the SEI film containing Li alone. From the above, it is presumed that the cycle characteristics are more likely to be improved.
[0023] The content of the negative electrode additive in the negative electrode mixture may be less than 8% by mass, preferably 7% by mass or less, more preferably 0.3% by mass or more and 7% by mass or less, and even more preferably 0.4% by mass or more and 2% by mass or less, based on the total amount of the negative electrode mixture (100% by mass). When the content of the negative electrode additive in the negative electrode mixture is 0.3% by mass or more based on the total amount of the negative electrode mixture, the hydrogen fluoride trapping effect is easily obtained. When the content of the negative electrode additive in the negative electrode mixture is 7% by mass or less based on the total amount of the negative electrode mixture, the hydrogen fluoride trapping effect and the effect of suppressing the shift of the negative electrode slurry to basicity are easily obtained in a well-balanced manner.
[0024] The content of the negative electrode additive in the negative electrode mixture (amount relative to the total amount of the negative electrode mixture) can be determined by the following method. For example, the negative electrode additive may be separated from a sample of the negative electrode mixture with a known mass, its mass may be determined, and its proportion in the sample of the negative electrode mixture may be determined. The negative electrode additive particles and a mixture of the negative electrode additive particles and the silicon-containing material particles can be separated from the negative electrode mixture by a known method.
[0025] The mass ratio of the negative electrode additive particles to the silicon-containing material particles may be obtained using an image of the cross section of the sample (such as a backscattered electron image) in the same manner as in the case of obtaining the content of the oxide of the Group 2 element in the negative electrode additive. The negative electrode additive particles and the silicon-containing material particles are distinguished from each other by observing the particle diameter and the inside of the particles, and the area ratio of the negative electrode additive particles to the silicon-containing material particles is obtained. The composition of the negative electrode additive is obtained by AES analysis. For the silicon-containing material, the composition of the matrix phase is obtained by AES analysis, and the content of the silicon particles dispersed in the matrix phase is obtained by Si-NMR. The specific gravity of each material is obtained from the composition. The content of the negative electrode additive in the negative electrode mixture is obtained based on each value obtained above. The area ratio of the negative electrode additive particles to the silicon-containing material particles may be regarded as a volume ratio.
[0026] (Acrylic resin) The acrylic resin contains at least a unit of (meth)acrylate. In this specification, "(meth)acrylic acid" means at least one selected from the group consisting of "acrylic acid" and "methacrylic acid". In the negative electrode slurry, the acrylic resin may contain both a unit of (meth)acrylic acid and a unit of (meth)acrylate. Since (meth)acrylic acid is a weak acid and (meth)acrylate is a salt of a weak acid, the acrylic resin may exhibit a buffering effect against the negative electrode additive, which is basic. Therefore, the shift of the negative electrode slurry to basicity due to the negative electrode additive is suppressed. The acrylic resin may also serve as a binder in the negative electrode mixture.
[0027] The ratio of hydrogen atoms of the carboxyl groups contained in the acrylic resin that are substituted with alkali metal atoms or the like (hereinafter referred to as the substitution rate) is preferably 70% or more and 80% or less, more preferably 90% or more. When an acrylic resin having a substitution rate within the above range is contained in the negative electrode slurry, the buffering effect of the acrylic resin is easily achieved, and the shift of the negative electrode slurry to basicity due to the negative electrode additive is efficiently suppressed. In addition, the negative electrode slurry is easy to prepare, which is advantageous for improving the battery characteristics.
[0028] Examples of (meth)acrylic acid salts include alkali metal salts such as lithium salts and sodium salts, ammonium salts, etc. Among them, from the viewpoint of reducing internal resistance, etc., lithium salts of (meth)acrylic acid are preferred, and lithium salts of acrylic acid are more preferred.
[0029] More specifically, the acrylic resin is a polymer containing at least a (meth)acrylic acid unit among the (meth)acrylic acid unit and the (meth)acrylic acid salt unit. The polymer may contain only a (meth)acrylic acid salt unit among the (meth)acrylic acid unit and the (meth)acrylic acid salt unit as a repeating unit. The polymer may further contain other units other than the (meth)acrylic acid unit and the (meth)acrylic acid salt unit. Examples of other units include ethylene units. In the polymer, the total of the (meth)acrylic acid unit and the (meth)acrylic acid salt unit is, for example, preferably 50 mol % or more, more preferably 80 mol % or more.
[0030] Specific examples of acrylic resins include polyacrylic acid, polymethacrylic acid, salts of copolymers containing repeating units of acrylic acid and / or methacrylic acid (acrylic acid-methacrylic acid copolymer, ethylene-acrylic acid copolymer, etc.) (substitution rate of 90% or more), etc. These may be used alone or in combination of two or more.
[0031] The weight-average molecular weight of the acrylic resin is preferably not less than 3,000 and not more than 10,000,000. When the weight-average molecular weight of the acrylic resin is within the above range, the effect of improving cycle characteristics and the effect of reducing internal resistance due to the acrylic resin are sufficiently obtained, and gelation (viscosity increase) of the negative electrode slurry is suppressed, making it easy to prepare the negative electrode.
[0032] The content of the acrylic resin in the negative electrode mixture may be 0.2 parts by mass or more and 2 parts by mass or less, or 0.4 parts by mass or more and 1.5 parts by mass or less, per 100 parts by mass of the negative electrode active material. When the content of the acrylic resin in the negative electrode mixture is 0.2 parts by mass or more per 100 parts by mass of the negative electrode active material, the effect of suppressing the shift of the negative electrode mixture to basicity is sufficiently obtained. When the content of the acrylic resin in the negative electrode mixture is 2 parts by mass or less per 100 parts by mass of the negative electrode active material, the increase in contact resistance between the negative electrode active material particles and between the negative electrode active material particles (negative electrode mixture layer) and the negative electrode current collector due to repeated charging and discharging is suppressed. In addition, the viscosity of the negative electrode slurry can be reduced, making it easy to prepare the negative electrode slurry. The amount of the negative electrode active material is sufficiently secured, making it easy to increase the capacity.
[0033] (Negative electrode active material) The negative electrode active material contains a silicon-containing material capable of electrochemically absorbing and releasing lithium ions, which is advantageous for increasing the capacity of the battery.
[0034] (1st composite material) The silicon-containing material may be a first composite material having a silicate phase containing at least one selected from the group consisting of an alkali metal element and a group 2 element, and silicon particles dispersed in the silicate phase. By controlling the amount of silicon particles dispersed in the silicate phase, a further increase in capacity is possible. Since the silicon particles are dispersed in the silicate phase, the expansion and contraction of the first composite material during charging and discharging is suppressed. Therefore, the first composite material is advantageous for increasing the capacity and improving the cycle characteristics of the battery.
[0035] The first composite material will be described in detail below. (silicon particles) From the viewpoint of suppressing cracks in the silicon particles themselves, the average particle size of the silicon particles is preferably 500 nm or less, more preferably 200 nm or less, and even more preferably 50 nm or less before the first charge. After the first charge, the average particle size of the silicon particles is preferably 400 nm or less, and more preferably 100 nm or less. By making the silicon particles finer, the volume change during charging and discharging is reduced, and the structural stability of the first composite material is further improved.
[0036] The average particle size of the silicon particles is measured by observing a cross-sectional SEM (scanning electron microscope) photograph of the first composite material. Specifically, the average particle size of the silicon particles is calculated by averaging the maximum diameters of 100 random silicon particles.
[0037] From the viewpoint of increasing the capacity, the content of silicon particles in the first composite material is preferably 30% by mass or more, more preferably 35% by mass or more, and even more preferably 55% by mass or more. In this case, the diffusibility of lithium ions is good, and excellent load characteristics are easily obtained. On the other hand, from the viewpoint of improving cycle characteristics, the content of silicon particles in the first composite material is preferably 80% by mass or less, and even more preferably 70% by mass or less. In this case, the surface of the silicon particles that is exposed without being covered with the silicate phase is reduced, and the reaction between the electrolyte and the silicon particles is easily suppressed.
[0038] The content of silicon particles can be measured by Si-NMR. The preferable measurement conditions for Si-NMR are shown below. Measurement equipment: Varian solid-state nuclear magnetic resonance spectrometer (INOVA-400) Probe: Varian 7mm CPMAS-2 MAS: 4.2kHz MAS speed: 4kHz Pulse: DD (45° pulse + signal acquisition time 1H decoupled) Repeat time: 1200sec Observation width: 100kHz Observation center: Around -100 ppm Signal acquisition time: 0.05 sec Accumulation count: 560 Sample size: 207.6mg
[0039] The silicon particles dispersed in the silicate phase have a particulate phase of silicon (Si) alone, and are composed of single or multiple crystallites. The crystallite size of the silicon particles is preferably 30 nm or less. When the crystallite size of the silicon particles is 30 nm or less, the volume change due to the expansion and contraction of the silicon particles accompanying charging and discharging can be reduced, and the cycle characteristics can be further improved. For example, when the silicon particles contract, voids are formed around the silicon particles, reducing the contact points with the surroundings of the particles, suppressing the isolation of the particles, and suppressing the decrease in charge and discharge efficiency due to the isolation of the particles. The lower limit of the crystallite size of the silicon particles is not particularly limited, but is, for example, 5 nm or more.
[0040] The crystallite size of the silicon particles is more preferably 10 nm or more and 30 nm or less, and further preferably 15 nm or more and 25 nm or less. When the crystallite size of the silicon particles is 10 nm or more, the surface area of the silicon particles can be kept small, so that the deterioration of the silicon particles accompanied by the generation of irreversible capacity is unlikely to occur. The crystallite size of silicon particles is calculated from the half-width of the diffraction peak assigned to the Si(111) plane in the X-ray diffraction (XRD) pattern of the silicon particles by Scherrer's formula.
[0041] (Silicate phase) The silicate phase contains at least one of an alkali metal element (Group 1 element other than hydrogen in the long-period periodic table) and a Group 2 element of the long-period periodic table. The alkali metal elements include lithium (Li), potassium (K), sodium (Na), etc. The Group 2 elements include magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), etc. The silicate phase contains at least one element of the alkali metal element and the Group 2 element, silicon (Si), and oxygen (O). As other elements, the silicate phase may include aluminum (Al), boron (B), lanthanum (La), phosphorus (P), zirconium (Zr), titanium (Ti), iron (Fe), chromium (Cr), nickel (Ni), manganese (Mn), copper (Cu), molybdenum (Mo), zinc (Zn), etc.
[0042] Since the irreversible capacity is small and the initial charge-discharge efficiency is high, the silicate phase is preferably a silicate phase containing lithium (hereinafter also referred to as a lithium silicate phase). That is, the first composite material is preferably a composite material (hereinafter also referred to as LSX or negative electrode material LSX) containing a lithium silicate phase and silicon particles dispersed in the lithium silicate phase. The lithium silicate phase contains at least lithium (Li), silicon (Si), and oxygen (O). The atomic ratio of O to Si in the lithium silicate phase: O / Si is, for example, greater than 2 and less than 4. When O / Si is greater than 2 and less than 4 (z in the formula described later is 0 < z < 2), it is advantageous in terms of stability and lithium ion conductivity. Preferably, O / Si is greater than 2 and less than 3 (z in the formula described later is 0 < z < 1). The atomic ratio of Li to Si in the lithium silicate phase: Li / Si is, for example, greater than 0 and less than 4. The lithium silicate phase may contain the above other elements in addition to Li, Si, and O.
[0043] The lithium silicate phase may have a composition represented by, for example, the formula: Li 2z SiO 2+z (0 < z < 2). From the viewpoints of stability, ease of production, lithium ion conductivity, etc., z preferably satisfies the relationship of 0 < z < 1, and z = 1 / 2 is more preferable.
[0044] The lithium silicate phase of LSX is SiO x Compared to the SiO2 phase, LSX has fewer sites that can react with lithium. x Compared to lithium silicate, it is less likely to cause irreversible capacity during charging and discharging. When silicon particles are dispersed in the lithium silicate phase, excellent charge and discharge efficiency can be obtained at the beginning of charging and discharging. In addition, since the content of silicon particles can be changed arbitrarily, a high-capacity anode can be designed.
[0045] The composition of the lithium silicate phase of the negative electrode material LSX can be analyzed, for example, by the following method. The battery is disassembled, the negative electrode is removed, washed with a non-aqueous solvent such as ethylene carbonate, and dried, and then the cross section of the negative electrode mixture layer is processed using a cross-section polisher (CP) to obtain a sample. A field emission scanning electron microscope (FE-SEM) is used to obtain a backscattered electron image of the sample cross section, and the cross section of the LSX particles is observed. An Auger electron spectroscopy (AES) analyzer is used to perform qualitative and quantitative elemental analysis of the lithium silicate phase of the observed LSX particles (accelerating voltage 10 kV, beam current 10 nA). The composition of the lithium silicate phase is determined based on the obtained contents of lithium (Li), silicon (Si), oxygen (O), and other elements.
[0046] The average particle size of the LSX particles (5 μm or more and 10 μm or less) is larger than that of the negative electrode additive particles (0.3 μm or more and 3 μm or less), and silicon particles are dispersed inside the LSX particles. Therefore, it is possible to distinguish between LSX particles and negative electrode additive particles by observing the particle size and the inside of the particles. In the cross-sectional observation and analysis of the above samples, a carbon sample stage can be used to fix the sample in place to prevent diffusion of Li. A transfer vessel can be used to hold and transport the sample without exposing it to the atmosphere to prevent deterioration of the sample cross section.
[0047] The first composite material preferably forms particulate materials (hereinafter also referred to as first particles) having an average particle size of 5 μm or more and 25 μm or less, more preferably 7 μm or more and 15 μm or less. Within the above particle size range, it is easy to relieve the stress caused by the volume change of the first composite material during charge and discharge, and it is easy to obtain good cycle characteristics. The surface area of the first particles also becomes appropriate, and the capacity reduction due to the side reaction with the electrolyte is also suppressed.
[0048] The average particle size of the first particles means the particle size (volume average particle size) at which the volume integration value is 50% in the particle size distribution measured by the laser diffraction scattering method. As the measuring device, for example, "LA-750" manufactured by Horiba, Ltd. can be used.
[0049] The first particles preferably include a conductive material that coats at least a part of their surface. Since the silicate phase has poor electron conductivity, the conductivity of the first particles tends to be low. By coating the surface with a conductive material, the conductivity can be dramatically increased. The conductive layer is preferably thin to such an extent that it does not substantially affect the average particle size of the first particles.
[0050] (Second composite material) The silicon-containing material may be a second composite material including a SiO2 phase and silicon particles dispersed in the SiO2 phase. The second composite material is represented by SiO x and satisfies 0 < x < 2. x may be 0.5 or more and 1.5 or less. The second composite material is advantageous in that the expansion during charging is small.
[0051] (Carbon material) The negative electrode active material may further include a carbon material that electrochemically absorbs and releases lithium ions. The carbon material expands and contracts less during charging and discharging than the silicon-containing material. By using the silicon-containing material and the carbon material in combination, the contact state between the negative electrode active material particles and between the negative electrode mixture layer and the negative electrode current collector can be better maintained during repeated charging and discharging. That is, the cycle characteristics can be improved while imparting the high capacity of the silicon-containing material to the negative electrode. From the viewpoint of increasing the capacity and improving the cycle characteristics, the ratio of the carbon material to the total of the silicon-containing material and the carbon material is preferably 98 mass% or less, more preferably 70 mass% or more and 98 mass% or less, and even more preferably 75 mass% or more and 95 mass% or less.
[0052] Examples of carbon materials used for the negative electrode active material include graphite, graphitizable carbon (soft carbon), and non-graphitizable carbon (hard carbon). Among them, graphite is preferred because it has excellent charge / discharge stability and low irreversible capacity. Graphite means a material having a graphite-type crystal structure, and includes, for example, natural graphite, artificial graphite, and graphitized mesophase carbon particles. The carbon material may be used alone or in combination of two or more kinds.
[0053] (Nonaqueous electrolyte secondary battery) Moreover, a nonaqueous electrolyte secondary battery according to an embodiment of the present invention includes a positive electrode, a negative electrode, and a nonaqueous electrolyte, and the negative electrode includes the above-mentioned negative electrode mixture.
[0054] The nonaqueous electrolyte secondary battery will be described in detail below. [Negative electrode] The negative electrode may include a negative electrode current collector and a negative electrode mixture layer supported on the surface of the negative electrode current collector. The negative electrode mixture layer can be formed by dispersing a negative electrode mixture containing a silicon-containing material, a negative electrode additive, and an acrylic resin in water to prepare a negative electrode slurry, applying the negative electrode slurry to the surface of the negative electrode current collector, and drying it. By including an acrylic resin in the negative electrode mixture (negative electrode slurry), the shift of the negative electrode slurry to basicity due to the negative electrode additive is suppressed. The coating film after drying may be rolled as necessary. The negative electrode mixture layer may be formed on one surface of the negative electrode current collector, or on both surfaces.
[0055] The negative electrode mixture contains, as essential components, a negative electrode active material, a negative electrode additive, and an acrylic resin. The negative electrode mixture may contain, as optional components, a binder other than the acrylic resin, a conductive agent, a thickener, etc. The negative electrode active material contains at least a silicon-containing material, and may further contain a carbon material.
[0056] As the negative electrode current collector, a non-porous conductive substrate (metal foil, etc.) or a porous conductive substrate (mesh, net, punched sheet, etc.) is used. Examples of the material of the negative electrode current collector include stainless steel, nickel, nickel alloy, copper, copper alloy, etc. The thickness of the negative electrode current collector is not particularly limited, but is preferably 1 to 50 μm, more preferably 5 to 20 μm, from the viewpoint of the balance between the strength and weight reduction of the negative electrode.
[0057] Examples of binders other than acrylic resins include fluororesins such as polytetrafluoroethylene and polyvinylidene fluoride (PVDF); polyolefin resins such as polyethylene and polypropylene; polyamide resins such as aramid resin; polyimide and polyamideimide; acrylic resins such as polyacrylic acid, polymethyl acrylate, and ethylene-acrylic acid copolymer; vinyl resins such as polyacrylonitrile and polyvinyl acetate; polyvinylpyrrolidone; polyethersulfone; and rubber-like materials such as styrene-butadiene copolymer rubber (SBR). One type of binder other than acrylic resin may be used alone, or two or more types may be used in combination.
[0058] Examples of the conductive agent include carbons such as acetylene black and carbon nanotubes, conductive fibers such as carbon fibers and metal fibers, carbon fluoride, metal powders such as aluminum, conductive whiskers such as zinc oxide and potassium titanate, conductive metal oxides such as titanium oxide, and organic conductive materials such as phenylene derivatives. One type of conductive agent may be used alone, or two or more types may be used in combination.
[0059] Examples of thickeners include carboxymethylcellulose (CMC) and its modified products (including salts such as Na salt), cellulose derivatives such as methylcellulose (cellulose ethers, etc.), saponified polymers having vinyl acetate units such as polyvinyl alcohol, polyethers (polyalkylene oxides such as polyethylene oxide, etc.), etc. One type of thickener may be used alone, or two or more types may be used in combination.
[0060] As the dispersion medium for the negative electrode slurry, a polar dispersion medium can be used, for example, water, alcohol such as ethanol, ether such as tetrahydrofuran, amide such as dimethylformamide, and N-methyl-2-pyrrolidone (NMP). The dispersion medium may be used alone or in combination of two or more.
[0061] [Positive electrode] The positive electrode may include, for example, a positive electrode current collector and a positive electrode mixture layer formed on the surface of the positive electrode current collector. The positive electrode mixture layer can be formed by applying a positive electrode slurry in which the positive electrode mixture is dispersed in a dispersion medium to the surface of the positive electrode current collector and drying it. The coating film after drying may be rolled as necessary. The positive electrode mixture layer may be formed on one surface of the positive electrode current collector or on both surfaces. The positive electrode mixture includes a positive electrode active material as an essential component, and may include a binder, a conductive agent, etc. as optional components. As the dispersion medium of the positive electrode slurry, those exemplified in the negative electrode slurry can be used.
[0062] As the positive electrode active material, for example, a lithium-containing composite oxide can be used.a CoO2, Li a NiO2, Li a MnO2, Li a Co b Ni 1-b O2, Li a Co b M 1-b O c , Li a Ni 1-b M b O c , Li a Mn2O4, Li a Mn 2-b M b O 4、 LiMPO 4、 Li2MPO4F (M is at least one selected from the group consisting of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, and B). Here, a = 0 to 1.2, b = 0 to 0.9, and c = 2.0 to 2.3. Note that the a value indicating the molar ratio of lithium increases or decreases during charge and discharge.
[0063] Among them, Li a Ni b M 1-b O2 (M is at least one selected from the group consisting of Mn, Co, and Al, 0 < a ≤ 1.2, and 0.3 ≤ b ≤ 1).) is preferable. From the viewpoint of increasing the capacity, it is more preferable to satisfy 0.85 ≤ b ≤ 1. From the viewpoint of the stability of the crystal structure, Li a Ni b Co c Al d O2 (0 < a ≤ 1.2, 0.85 ≤ b < 1, 0 < c < 0.15, 0 < d ≤ 0.1, b + c + d = 1) is even more preferable.
[0064] As the binder and the conductive agent, the same ones as those exemplified for the negative electrode can be used. As the binder, an acrylic resin may be used. As the conductive agent, graphite such as natural graphite and artificial graphite may be used.
[0065] The shape and thickness of the positive electrode current collector can be selected from the shape and range corresponding to those of the negative electrode current collector. Examples of the material of the positive electrode current collector include stainless steel, aluminum, aluminum alloy, titanium, etc.
[0066] [Nonaqueous electrolyte] The non-aqueous electrolyte includes a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent. The concentration of the lithium salt in the non-aqueous electrolyte is preferably, for example, 0.5 mol / L or more and 2 mol / L or less. By setting the lithium salt concentration in the above range, a non-aqueous electrolyte having excellent ion conductivity and appropriate viscosity can be obtained. However, the lithium salt concentration is not limited to the above.
[0067] Examples of lithium salts include LiClO4, LiBF4, LiPF6, LiAlCl4, LiSbF6, LiSCN, LiCF3SO3, LiCF3CO2, LiAsF6, LiB 10 Cl 10 , lower aliphatic lithium carboxylates, LiCl, LiBr, LiI, borates, imide salts, etc. Examples of borates include lithium bis(1,2-benzenedioleate(2-)-O,O')borate, lithium bis(2,3-naphthalenediolate(2-)-O,O')borate, lithium bis(2,2'-biphenyldioleate(2-)-O,O')borate, lithium bis(5-fluoro-2-oleate-1-benzenesulfonic acid-O,O')borate, etc. Examples of imide salts include lithium bis(fluorosulfonyl)imide (LFSI), lithium bistrifluoromethanesulfonate imide (LiN(CF3SO2)2), lithium trifluoromethanesulfonate nonafluorobutanesulfonate imide (LiN(CF3SO2)(C4F9SO2)), lithium bispentafluoroethanesulfonate imide (LiN(C2F5SO2)2), etc. Among these, LiPF6 is preferred. LiPF6 is easy to form a passive film on the surface of the components constituting the battery, such as the outer can. The passive film can protect the above-mentioned components. The lithium salt may be used alone or in combination of two or more kinds.
[0068] Examples of the non-aqueous solvent include cyclic carbonates, chain carbonates, cyclic carboxylates, and chain carboxylates. Examples of the cyclic carbonates include propylene carbonate (PC) and ethylene carbonate (EC). Examples of the chain carbonates include diethyl carbonate (DEC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC). Examples of the cyclic carboxylates include γ-butyrolactone (GBL) and γ-valerolactone (GVL). Examples of the chain carboxylates include methyl formate, ethyl formate, propyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, and propyl propionate. The non-aqueous solvent may be used alone or in combination of two or more.
[0069] [Separator] Usually, it is desirable to interpose a separator between the positive electrode and the negative electrode. The separator has high ion permeability and has appropriate mechanical strength and insulation properties. As the separator, a microporous thin film, a woven fabric, a nonwoven fabric, etc. can be used. As the material of the separator, polyolefin such as polypropylene and polyethylene is preferable.
[0070] An example of the structure of the non-aqueous electrolyte secondary battery is a structure in which an electrode group formed by winding a positive electrode and a negative electrode with a separator interposed therebetween and a non-aqueous electrolyte are housed in an exterior body. Alternatively, instead of a wound type electrode group, an electrode group of another form, such as a stacked type electrode group formed by stacking a positive electrode and a negative electrode with a separator interposed therebetween, may be applied. The non-aqueous electrolyte secondary battery may be in any form, such as a cylindrical type, a square type, a coin type, a button type, a laminate type, or the like.
[0071] Hereinafter, as one example of the nonaqueous electrolyte secondary battery according to the present invention, the structure of a prismatic nonaqueous electrolyte secondary battery will be described with reference to Fig. 1. Fig. 1 is a schematic perspective view of a nonaqueous electrolyte secondary battery according to one embodiment of the present invention, with a portion cut away.
[0072] The battery includes a bottomed rectangular battery case 4, and an electrode group 1 and an electrolyte (not shown) housed in the battery case 4. The electrode group 1 includes a long strip-shaped negative electrode, a long strip-shaped positive electrode, and a separator interposed between them to prevent direct contact. The electrode group 1 is formed by winding the negative electrode, positive electrode, and separator around a flat plate-shaped winding core and removing the winding core.
[0073] One end of the negative electrode lead 3 is attached to the negative electrode current collector of the negative electrode by welding or the like. The other end of the negative electrode lead 3 is electrically connected to a negative electrode terminal 6 provided on the sealing plate 5 via a resin insulating plate (not shown). The negative electrode terminal 6 is insulated from the sealing plate 5 by a resin gasket 7. One end of the positive electrode lead 2 is attached to the positive electrode current collector of the positive electrode by welding or the like. The other end of the positive electrode lead 2 is connected to the back surface of the sealing plate 5 via an insulating plate. That is, the positive electrode lead 2 is electrically connected to the battery case 4 which also serves as the positive electrode terminal. The insulating plate separates the electrode group 1 and the sealing plate 5, and separates the negative electrode lead 3 and the battery case 4. The periphery of the sealing plate 5 is fitted into the open end of the battery case 4, and the fitting portion is laser welded. In this way, the opening of the battery case 4 is sealed with the sealing plate 5. The electrolyte injection hole provided in sealing plate 5 is closed with a sealing plug 8 . EXAMPLES
[0074] Examples of the present invention will be specifically described below, but the present invention is not limited to the following examples.
[0075] Example 1 [Preparation of negative electrode] Water was added to the negative electrode mixture, and the mixture was stirred using a mixer (TK Hivismix, manufactured by Primix Corporation) to prepare a negative electrode slurry. The negative electrode mixture was a mixture of a negative electrode active material, a negative electrode additive, a lithium salt of polyacrylic acid (PAA-Li), sodium carboxymethylcellulose (CMC-Na), and styrene-butadiene rubber (SBR).
[0076] A mixture of silicon-containing material and graphite was used as the negative electrode active material. The ratio of graphite to the total of silicon-containing material and graphite was set to 95 mass %. For the silicon-containing material, particles of SiO (x=1) (average particle size 5 to 10 μm) were used as the second composite material.
[0077] The negative electrode additive was a powdered glass (average particle size 1 μm) containing silicon dioxide (SiO2), Li2O, an oxide of an alkali metal element, and CaO, an oxide of a Group 2 element. The contents of SiO2, Li2O, and CaO in the negative electrode additive were 74.4 mass%, 8.2 mass%, and 17.4 mass%, respectively. In Tables 1 to 3, "Bal." for the SiO2 content indicates the remaining amount. The content of the negative electrode additive in the negative electrode mixture was 0.5 parts by mass per 100 parts by mass of the negative electrode active material.
[0078] The PAA-Li used had a substitution rate of 100%. The content of PAA-Li in the negative electrode mixture was 0.7 parts by mass per 100 parts by mass of the negative electrode active material. The content of CMC-Na in the negative electrode mixture was 1 part by mass per 100 parts by mass of the negative electrode active material. The content of SBR in the negative electrode mixture was 1 part by mass per 100 parts by mass of the negative electrode active material.
[0079] Next, apply 1 m 2 The negative electrode slurry was applied so that the mass of the negative electrode mixture per sheet was 190 g, the coating was dried, and then rolled to give a density of 1.5 g / cm on both sides of the copper foil. 3 A negative electrode mixture layer was formed, thereby obtaining a negative electrode.
[0080] [Preparation of positive electrode] Lithium nickel composite oxide (LiNi 0.8 Co 0.18 Al 0.02O2), acetylene black, and polyvinylidene fluoride were mixed in a mass ratio of 95:2.5:2.5, N-methyl-2-pyrrolidone (NMP) was added, and the mixture was stirred using a mixer (TK Hivismix, manufactured by Primix Corporation) to prepare a positive electrode slurry. Next, the positive electrode slurry was applied to the surface of an aluminum foil, the coating was dried, and then rolled to form a positive electrode slurry with a density of 3.6 g / cm on both sides of the aluminum foil. 3 A positive electrode mixture layer was formed to obtain a positive electrode.
[0081] [Preparation of non-aqueous electrolyte] A non-aqueous electrolyte was prepared by dissolving a lithium salt in a non-aqueous solvent. The non-aqueous solvent was a mixture of ethylene carbonate (EC) and dimethyl carbonate (DMC) in a volume ratio of 3:7. LiPF6 was used as the lithium salt. The concentration of LiPF6 in the non-aqueous electrolyte was 1.0 mol / L.
[0082] [Preparation of non-aqueous electrolyte secondary battery] A tab was attached to each electrode, and the positive and negative electrodes were spirally wound with a separator interposed therebetween so that the tabs were located at the outermost periphery to prepare an electrode group. The electrode group was inserted into an exterior body made of an aluminum laminate film and vacuum dried at 105°C for 2 hours. After that, a nonaqueous electrolyte was poured in and the opening of the exterior body was sealed to obtain a battery A1.
[0083] The negative electrode slurry and the battery prepared above were evaluated as follows. [Evaluation 1: pH of negative electrode slurry] The negative electrode slurry used in the production of the battery A1 was prepared, and the pH of the negative electrode slurry at 25° C. was measured.
[0084] [Evaluation 2: Capacity retention rate after 150 cycles] Battery A1 was charged at a constant current of 0.3 It (990 mA) until the voltage reached 4.2 V, and then charged at a constant voltage of 4.2 V until the current reached 0.015 It (50 mA). It was then discharged at a constant current of 0.3 It (990 mA) until the voltage reached 2.75 V. The rest time between charging and discharging was 10 minutes. Charging and discharging were performed in an environment of 25°C. Charge and discharge were repeated under the above conditions. The ratio of the discharge capacity at the 150th cycle to the discharge capacity at the 1st cycle was calculated as the capacity retention rate. The capacity retention rate was expressed as an index with the capacity retention rate of Battery B1 set at 100.
[0085] Example 2 Batteries A2 to A6 were produced in the same manner as battery A1, except that the content of each component in the negative electrode additive was set to the value shown in Table 1. The content of each component in the negative electrode additive in Table 1 is the mass ratio (mass%) to the total amount of the negative electrode additive. In Table 1, Li2O and Na2O are oxides of alkali metal elements, and BaO, CaO, and MgO are oxides of Group 2 elements.
[0086] Comparative Example 1 Battery B1 was produced in the same manner as Battery A1, except that the negative electrode mixture did not contain the negative electrode additive and PAA-Li. Battery B2 was produced in the same manner as Battery A1, except that the negative electrode mixture did not contain PAA-Li. Battery B3 was produced in the same manner as Battery A1, except that the negative electrode mixture did not contain the negative electrode additive. Batteries B4 to B5 were produced in the same manner as Battery A1, except that the contents of each component in the negative electrode additive were set to the values shown in Table 1. Batteries B1 to B5 were evaluated in the same manner as Battery A1. Table 1 shows the evaluation results of the batteries A1 to A6 and B1 to B5.
[0087] [Table 1]
[0088] Battery A1, in which the content of an oxide of a Group 2 element (CaO) in the negative electrode additive was less than 20 mass% relative to the total amount of the negative electrode additive, achieved a high capacity retention rate and significantly improved cycle characteristics. Battery A1 showed a very large improvement in capacity retention rate of 25% compared to Battery B1, and compared to Battery B4, in which the content of an oxide of a Group 2 element (CaO) in the negative electrode additive was 20 mass% or more relative to the total amount of the negative electrode additive, the improvement in capacity retention rate was significantly greater than that of Battery B1. Battery B4 showed a small improvement in capacity retention rate of 10% compared to Battery B1. The negative electrode slurry used in producing Battery A1 had a lower pH than the negative electrode slurry used in producing Battery B4, and the pH was significantly lower than that of the negative electrode slurry used in producing Battery B2.
[0089] In battery A6, in which the content of the oxide of a Group 2 element (BaO) in the negative electrode additive is less than 20 mass% relative to the total amount of the negative electrode additive, the improvement in capacity retention rate relative to battery B1 was significantly greater than in battery B5, in which the content of the oxide of a Group 2 element (BaO) in the negative electrode additive is 20 mass% or more relative to the total amount of the negative electrode additive.
[0090] Even in batteries A2 to A6, in which the content of the oxide of a Group 2 element (CaO) in the negative electrode additive was less than 20 mass% relative to the total amount of the negative electrode additive, the improvement in capacity retention rate relative to battery B1 was significantly greater than in battery B4, in which the content of the oxide of a Group 2 element (CaO) in the negative electrode additive was 20 mass% or more relative to the total amount of the negative electrode additive. In particular, in batteries A1 to A3, in which the content of CaO in the negative electrode additive was 10 mass% or more and 19.5 mass% or less relative to the total amount of the negative electrode additive, a high capacity retention rate of 120 or more was obtained.
[0091] Battery B1, which used a negative electrode mixture that did not contain a negative electrode additive or PAA-Li, showed a low capacity retention rate. Battery B2, which contained a negative electrode additive but did not contain PAA-Li, showed that the negative electrode additive reduced hydrogen fluoride, but the negative electrode slurry shifted to a basic state, degrading the silicon-containing material, resulting in little improvement in cycle characteristics. Battery B3, which contained PAA-Li but did not contain a negative electrode additive, showed that PAA-Li acted as a binder, but the silicon-containing material was degraded by hydrogen fluoride, resulting in little improvement in cycle characteristics.
[0092] The negative electrode slurry used in the preparation of battery B2 had a higher pH than the negative electrode slurry used in the preparation of battery B1 because the negative electrode mixture contained a negative electrode additive. The negative electrode slurry used in the preparation of batteries A1 to A6 had a lower pH than the negative electrode slurry used in the preparation of battery B2 because the negative electrode mixture contained PAA-Li together with the negative electrode additive.
[0093] Example 3 Batteries A7 to A8 were produced and evaluated in the same manner as battery A1, except that the content of each component in the negative electrode additive was set to the value shown in Table 2. The evaluation results are shown in Table 2. The content of each component in the negative electrode additive in Table 2 is the mass ratio (mass%) to the total amount of the negative electrode additive. In Table 2, Li2O and Na2O are oxides of alkali metal elements, and BaO, CaO, and MgO are oxides of Group 2 elements.
[0094] Example 4 [Preparation of negative electrode material LSX] Silicon dioxide and lithium carbonate were mixed so that the atomic ratio: Si / Li was 1.05, and the mixture was calcined in air at 950°C for 10 hours to obtain lithium silicate represented by Li2Si2O5 (z=1 / 2). The obtained lithium silicate was pulverized to an average particle size of 10 μm.
[0095] Lithium silicate (Li2Si2O5) with an average particle size of 10 μm was mixed with raw silicon (3N, average particle size of 10 μm) in a mass ratio of 45:55. The mixture was loaded into a pot (made of SUS, volume: 500 mL) of a planetary ball mill (manufactured by Fritsch, P-5), 24 SUS balls (diameter 20 mm) were placed in the pot, the lid was closed, and the mixture was milled at 200 rpm for 50 hours in an inert atmosphere.
[0096] Next, the powder mixture was taken out in an inert atmosphere, and sintered at 800°C for 4 hours in an inert atmosphere while applying pressure using a hot press machine, to obtain a sintered body of the mixture (negative electrode material LSX).
[0097] The negative electrode material LSX was then crushed and passed through a 40 μm mesh, after which the resulting LSX particles were mixed with coal pitch (MCP250, manufactured by JFE Chemical Corporation), and the mixture was fired at 800°C in an inert atmosphere to form a conductive layer containing conductive carbon on the surface of the LSX particles. The amount of the conductive layer was 5 mass% based on the total mass of the LSX particles and the conductive layer. Then, LSX particles (average particle size 5 μm) having a conductive layer were obtained using a sieve.
[0098] The crystallite size of the silicon particles was calculated to be 15 nm using the Scherrer formula from the diffraction peaks assigned to the Si(111) plane by XRD analysis of the LSX particles. The content of silicon particles in the LSX particles was 55 mass% as measured by Si-NMR.
[0099] Batteries C1 to C3 were fabricated and evaluated in the same manner as for the batteries A1, A7, and A8, except that the LSX having the conductive layer obtained above was used as the first composite material for the silicon-containing material. The evaluation results are shown in Table 2.
[0100] [Table 2]
[0101] All of the batteries A1 and A7 to A8 exhibited high capacity retention rates. Among them, the batteries A7 to A8, which used a negative electrode additive containing Na2O, exhibited higher capacity retention rates of 135 or more.
[0102] The batteries C1 to C3 using LSX as the silicon-containing material had a higher capacity retention rate than the batteries A1, A7 to A8 using SiO as the silicon-containing material. Among them, the batteries C2 to C3 using the negative electrode additive containing Na2O had a particularly high capacity retention rate of about 150.
[0103] Example 5 Batteries A9 to A10 were produced and evaluated in the same manner as for Battery A1, except that the content of PAA-Li in the negative electrode mixture was set to the value shown in Table 3. The content of PAA-Li in Table 3 is the amount (parts by mass) per 100 parts by mass of the negative electrode active material. Batteries A11 and A12 were produced and evaluated in the same manner as for Battery A1, except that the content of the negative electrode additive in the negative electrode mixture was set to the value shown in Table 3. The content of the negative electrode additive in Table 3 is the amount (parts by mass) per 100 parts by mass of the negative electrode active material. The batteries A9 to A12 were evaluated in the same manner as the battery A1. The evaluation results are shown in Table 3.
[0104] [Table 3]
[0105] In the batteries A1, A9 to A10, in which the content of PAA-Li in the negative electrode mixture was 0.2 parts by mass or more and 2.0 parts by mass or less per 100 parts by mass of the negative electrode active material, a high capacity retention rate was obtained and cycle characteristics were improved. In the batteries A1, A11 to A12, in which the content of the negative electrode additive in the negative electrode mixture was 0.3% by mass or more and 7% by mass or less with respect to the total amount of the negative electrode mixture, a high capacity retention rate was obtained. [Industrial Applicability]
[0106] The nonaqueous electrolyte secondary battery according to the present invention is useful as a main power source for mobile communication devices, portable electronic devices, and the like. Although the present invention has been described with respect to the presently preferred embodiments, such disclosure should not be interpreted as limiting. Various variations and modifications will no doubt become apparent to those skilled in the art to which the present invention pertains upon reading the above disclosure. Accordingly, the appended claims should be interpreted to cover all variations and modifications without departing from the true spirit and scope of the present invention. [Explanation of symbols]
[0107] 1: electrode group, 2: positive electrode lead, 3: negative electrode lead, 4: battery case, 5: sealing plate, 6: negative electrode terminal, 7: gasket, 8: sealing plug
Claims
1. The battery includes a negative electrode mixture including a negative electrode active material capable of electrochemically absorbing and releasing lithium ions, a negative electrode additive, and an acrylic resin; the negative electrode active material includes a silicon-containing material, The negative electrode additive is silicon dioxide and an oxide of a Group 2 element; The oxide of the Group 2 element includes at least one selected from the group consisting of BeO, MgO, CaO, SrO, BaO, and RaO, The acrylic resin contains at least a (meth)acrylate unit, The content of the negative electrode additive in the negative electrode mixture is less than 8 mass% with respect to the total amount of the negative electrode mixture, The content of the oxide of the Group 2 element in the negative electrode additive is less than 20 mass% with respect to the total amount of the negative electrode additive, The negative electrode for a nonaqueous electrolyte secondary battery, wherein the content of the acrylic resin in the negative electrode mixture is 0.2 parts by mass or more and 2 parts by mass or less per 100 parts by mass of the negative electrode active material.
2. A battery comprising a negative electrode mixture including a negative electrode active material capable of electrochemically absorbing and releasing lithium ions, a negative electrode additive, and an acrylic resin; the negative electrode active material includes a silicon-containing material, The negative electrode additive is silicon dioxide, an oxide of a Group 2 element, and an oxide of an alkali metal element; The oxide of the Group 2 element includes at least one selected from the group consisting of BeO, MgO, CaO, SrO, BaO, and RaO, The oxide of the alkali metal element includes at least one selected from the group consisting of Li 2 O, Na 2 O, and K 2 O, The acrylic resin contains at least a (meth)acrylate unit, The content of the negative electrode additive in the negative electrode mixture is less than 8 mass% with respect to the total amount of the negative electrode mixture, The content of the oxide of the Group 2 element in the negative electrode additive is less than 20 mass% with respect to the total amount of the negative electrode additive, The negative electrode for a nonaqueous electrolyte secondary battery, wherein the content of the acrylic resin in the negative electrode mixture is 0.2 parts by mass or more and 2 parts by mass or less per 100 parts by mass of the negative electrode active material.
3. 3. The negative electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein the oxide of the Group 2 element includes at least one selected from the group consisting of BaO and CaO.
4. The oxide of the alkali metal element is Na 2 The negative electrode for a nonaqueous electrolyte secondary battery according to claim 2 , further comprising O.
5. The content of the negative electrode additive in the negative electrode mixture is 0.3 mass% or more and 7 mass% or less with respect to the total amount of the negative electrode mixture. The negative electrode for a nonaqueous electrolyte secondary battery according to any one of claims 1 to 4.
6. 6. The negative electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein the (meth)acrylate salt is a lithium salt of (meth)acrylic acid.
7. The silicon-containing material includes a composite material having a silicate phase and silicon particles dispersed within the silicate phase; 7. The negative electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein the silicate phase contains at least one selected from the group consisting of alkali metal elements and Group 2 elements.
8. 8. The negative electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein the negative electrode active material further comprises a carbon material.
9. 9. The negative electrode for a nonaqueous electrolyte secondary battery according to claim 1, comprising: a negative electrode current collector; and a layer supported on a surface of the negative electrode current collector and containing the negative electrode mixture.
10. The battery includes a positive electrode, a negative electrode, and a non-aqueous electrolyte solution, The negative electrode of any one of claims 1 to 9, wherein the negative electrode is a non-aqueous electrolyte secondary battery.
11. The non-aqueous electrolyte is LiPF 6 The nonaqueous electrolyte secondary battery according to claim 10 .
Citation Information
Patent Citations
Battery cell components having inorganic components with low thermal conductivity
JP2013524418A
Additives for electrochemical energy storage devices, and electrochemical energy storage devices
JP2015532762A
Anode composition for rechargeable batteries and method of making same
JP2017517121A
Negative-electrode active material for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery
WO2016121320A1